A validity and reliability of the atraumatic care education model questionnaire based on family-centred care in minimising the stress of hospitalisation in children - Alfiyanti Dera; Sufyanti Arief Yuni; Krisnana Ilya; Triharini Mira; Pranata Satriya (Scripta Medica)
Background/Aim: Hospitalisation is a traumatic occurrence in which children must be admitted for acute or chronic diseases. The purpose of this study was to test the validity and reliability of the atraumatic care education model test, instrument based on family-centred care of mother behaviour in minimising children's hospitalisation stress. Methods: Questionnaires were developed based on each parameter of each variable. After the questionnaires were developed, the researcher conducted a pilot study with 50 respondents to assess their validity and reliability. The validity test used the Product Moment test, while the reliability test used Croncbach's Alpha value. Results: All questionnaire statement items on the nurse factor, the mother factor, the service factor, the learning process, the atraumatic care education factor and on mother behaviour variables were declared valid (r count = 0.280-0.854), (r count = 0.292-0.767), (r count = 0.517-0.779), (r count = 0.737-0.918), (r count = 0.303-0.781; r table = 0.275) and (r count = 0.315-0.815; r table = 0.275), respectively. All questionnaires to measure nurse factors, maternal factors, service factors, learning process factors, atraumatic care education, maternal behaviour variables and distress questionnaires were reliable. The internal consistency (alpha coefficient) of the total scale ranged between 0.713-0.925. Conclusion: All questionnaires developed to assess the atraumatic care education model based on family-centred care on mother behaviour in minimising children's hospitalisation stress were valid and reliable and thus have certain application value.